Evaluación del efecto de dos productos promotores del enraizamiento en la calidad de almácigo de Café (Coffea Arabica L. Cv. Obatá), en Naranjo, Alajuela, Costa Rica - Steller-Jiménez, Ericks Danilo (Instituto Tecnológico de Costa Rica, 2018)
This study evaluated the quality of coffee seedling plants in response to the application of rooting promoters (Green Sol 48® and Green Sol 70® from BioAgro®), at three different doses each. The variables used as response indicators were: root length, stem length, stem thickness, number of leaves, leaf area, number of knots, fresh weight of the aerial part, fresh weight of the root, dry weight of the part aerial and dry weight of the root. Additionally, a group of producers made a qualitative assessment of the best treatments. The evaluation of the products began in November of the year 2017 and extended until February 2018 in the facilities of CooproNaranjo R.L located in Naranjo, Alajuela, Costa Rica. We used 280 coffee plants of the Obatá variety, where the experimental unit was composed of four plants; each treatment had ten replications, with the experimental area being 70 experimental units. The distribution of the experimental units was carried out randomly in the land where the nursery plants were located. In general, the Green Sol 70® treatments in commercial doses and 50% Green Sol 48® showed a better response in the quality of the variables studied with respect to the Control. According to an estimate of costs, the application of the treatments at the established doses would generate an increase in the maintenance price per plant, but it would shorten the time to transplant to the field and improve the quality of the variables studied.
Tesis (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2018.
Keywords: Producción agrícola; Cultivos agrícolas; Planta; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Agronomy